2020
DOI: 10.1073/pnas.2001768117
|View full text |Cite
|
Sign up to set email alerts
|

ChiS is a noncanonical DNA-binding hybrid sensor kinase that directly regulates the chitin utilization program in Vibrio cholerae

Abstract: Two-component signal transduction systems (TCSs) represent a major mechanism that bacteria use to sense and respond to their environment. Prototypical TCSs are composed of a membrane-embedded histidine kinase, which senses an environmental stimulus and subsequently phosphorylates a cognate partner protein called a response regulator that regulates gene expression in a phosphorylation-dependent manner. Vibrio cholerae uses the hybrid histidine kinase ChiS to activate the expression of the chitin utilization pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 57 publications
1
39
0
Order By: Relevance
“…Previous work from our group demonstrated that ChiS is a noncanonical hybrid histidine kinase that contains a DBD at its C terminus ( Fig. 1A ) ( 5 ). In that study, we found that the C-terminal 106 amino acids of ChiS (ChiS 1024–1129 ) were necessary and sufficient to bind to the chb promoter in vivo .…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Previous work from our group demonstrated that ChiS is a noncanonical hybrid histidine kinase that contains a DBD at its C terminus ( Fig. 1A ) ( 5 ). In that study, we found that the C-terminal 106 amino acids of ChiS (ChiS 1024–1129 ) were necessary and sufficient to bind to the chb promoter in vivo .…”
Section: Resultsmentioning
confidence: 91%
“…Chitin is sensed in V. cholerae by the hybrid histidine kinase ChiS ( 5 7 ). In response to chitin, ChiS activates the expression of the chitin utilization program.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analytical ultracentrifugation studies also showed that TMAO binding to apoTorT increases its affinity for TorS-LBD, a finding that was also reflected in decreased atomic mobility at the TorS-LBD/TorT interface. In a similar way, the CBP SBP interacts with the non-canonical DNA binding sensor kinase ChiS to repress its activity, and the binding of chitin oligosaccharides by the CBP/ChiS complex activates ChiS without triggering the dissociation of the complex [58] . Of note is that these findings do not agree with a previous publication that suggested a ligand-induced dissociation of CBP from ChiS [59] .…”
Section: Sensor Kinases Diguanylate Cyclases/phosphodiesterases and Ser/thr Kinasesmentioning
confidence: 99%
“…Via secreted chitinases, V. cholerae breaks down the chitin polymers and use the oligomers, detected by the HK ChiS, as their sole source of carbon and nitrogen. 28 30 …”
Section: Navigating the Aquatic Environment: Watch And Roll With The mentioning
confidence: 99%